Brand Awareness Wardah Cosmetics Users at ASN in Blitar Regency - Neni Utami; Nurul Farida (Indonesian Economic Review, 2023)
This research aims to determine the influence of brand ambassadors on the brand equity of Wardah cosmetic products among ASN in Blitar district. The research data used was primary data taken by distributing questionnaires using a Likert scale to 87 respondents out of 105 respondents who met the criteria. The research method used is an associative quantitative method, the data obtained is analyzed using validity and reliability tests, normality tests, simple regression tests, hypothesis tests and coefficient of determination tests. The results of the research show that the use of brand ambassadors can have a positive influence on brand awareness of Wardah cosmetic products among Blitar district ASN. Wardah cosmetics brand ambassadors who are able to increase brand awareness are transference brand ambassadors